The Influence of Word of Mouth and Brand Image on Consumer Purchase Intention at Irma Butique Clothing Store - Ila Lestia; Yulaikah; Suhroji Adha (Indonesia Economic Journal, 2025)
The purpose of this study is to examine the influence of word of mouth and brand image on consumer purchase intention at the Irma Butique clothing store. This study was conducted using a quantitative method, with a population and sample of 60 people. The data collection technique used a questionnaire and was distributed directly to customers of the Irma Butique store. Data analysis used SmartPLS. The results of the study show that word of mouth has an influence on purchase intention because the t-statistic value is 11.957 > t-table 1.96 and the significance p-value is 0.000 < 0.05, so word of mouth can be used as a measure of the level of purchase intention, especially at the Irma Butique Clothing Store. Brand image has a positive influence on purchase intention because the t-statistic value is 44.577 > t-table 1.96 and the significance p-value is 0.000 < 0.05; the better the brand image, the more it will affect the purchase intention of clothing at Irma Butique, and vice versa. Word of mouth and brand image have a positive simultaneous effect on purchase intention because the variability of the word of mouth and brand image constructs is 0.898. This shows that simultaneously they are able to explain the variability of the word of mouth and brand image constructs by 89.8%, while the remaining 10.1% is influenced by other factors. Therefore, the better the word of mouth and brand image, the more they will influence the purchase intention of clothing at Irma Butique, and vice versa.